Typification and taxonomic notes on three irises names (Iridaceae) described from Central Asia - Boltenkov, Eugeny V. (Phytotaxa, 2019)
Nomenclature issues of three irises names described from Central Asia (Iris alberti, I. eulefeldii, and I. humilis f. foliata) are here discussed. Particularly, a second-step lectotypification for I. alberti and lectotypifications for I. eulefeldii (a taxonomic synonym of I. scariosa) and I. humilis f. foliata (a taxonomic synonym of I. longiscapa) are provided.